Effect of size on spawning of Imbaw, Anodontia edentula (Linnaeus, 1758) - Cambel, Marianne Ponce (2008.)
The effect of shell size to spawning of Imbaw. Anodontia edentula was examined. A total of 120 clams with shell length ranging from 34.90 to 68.20 mm were collected. Basing on shell length, 3 class sizes were used group these clams, namely : < 45 mm, 45-50 mm, and > 50 mm. Thirty-five percent of theclams had shell length of < 45 mm, 21.7% in the range of 45-50 mm, and 43.3% had shell length of > 50 mm. Overall result showed that a high percentage of the clams in the range of 35 to 50 mm responded to spawning induction.
Special Problem (Undergraduate, Bachelor of Science in Biology) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo
Keywords: Imbaw -- spawning; Anodontia edentula